Molecular mechanisms of retinal ganglion cell degeneration in glaucoma and future prospects for cell body and axonal protection - Munemasa, Yasunari; Kitaoka, Yasushi (Frontiers in Cellular Neuroscience, 2013)
Glaucoma, which affects more than 70 million people worldwide, is a heterogeneous group of disorders with a resultant common denominator; optic neuropathy, eventually leading to irreversible blindness. The clinical manifestations of primary open-angle glaucoma (POAG), the most common subtype of glaucoma, include excavation of the optic disc and progressive loss of visual field. Axonal degeneration of retinal ganglion cells (RGCs) and apoptotic death of their cell bodies are observed in glaucoma, in which the reduction of intraocular pressure is known to slow progression of the disease. A pattern of localized retinal nerve fiber layer defects in glaucoma patients indicates that axonal degeneration may precede RGC body death in this condition. The mechanisms of degeneration of neuronal cell bodies and their axons may differ. In this review, we addressed the molecular mechanisms of cell body death and axonal degeneration in glaucoma and proposed axonal protection in addition to cell body protection. The concept of axonal protection may become a new therapeutic strategy to prevent further axonal degeneration or revive dying axons in patients with preperimetric glaucoma. Further study will be needed to clarify whether the combination therapy of axonal protection and cell body protection will have greater protective effects in early or progressive glaucomatous optic neuropathy.